Transcriptional Regulators of Ecdysteroid Biosynthetic Enzymes and Their Roles in Insect Development - Kamiyama, Takumi; Niwa, Ryusuke (Frontiers in Physiology, 2022)
Steroid hormones are responsible for coordinating many aspects of biological processes in most multicellular organisms, including insects. Ecdysteroid, the principal insect steroid hormone, is biosynthesized from dietary cholesterol or plant sterols. In the last 20 years, a number of ecdysteroidogenic enzymes, including Noppera-bo, Neverland, Shroud, Spook/Spookier, Cyp6t3, Phantom, Disembodied, Shadow, and Shade, have been identified and characterized in molecular genetic studies using the fruit fly Drosophila melanogaster. These enzymes are encoded by genes collectively called the Halloween genes. The transcriptional regulatory network, governed by multiple regulators of transcription, chromatin remodeling, and endoreplication, has been shown to be essential for the spatiotemporal expression control of Halloween genes in D. melanogaster. In this review, we summarize the latest information on transcriptional regulators that are crucial for controlling the expression of ecdysteroid biosynthetic enzymes and their roles in insect development.